Response to treatment is more important than disease severity at diagnosis for prediction of early relapse in new‐onset paediatric Crohn's disease. Issue 11 (18th November 2018) - Ziv‐Baran, Tomer; Hussey, Séamus; Sladek, Malgorzata; Amil Dias, Jorge; Martin de Carpi, Javier; Miele, Erasmo; Veres, Gabor; Lionetti, Paolo; Koletzko, Sibylle; Nuti, Federica; Paerregaard, Anders; Kolho, Kaija‐Leena; et al.
Summary: Background: Paediatric Crohn's disease is characteried by frequently relapsing disease which may lead to hospitalisations and complications. Aim: To develop predictive models for early relapse following first remission. Methods: The GROWTH CD prospective inception cohort was designed to predict risk for early disease relapse and poor outcomes. Newly diagnosed children underwent endoscopies and imaging. They were phenotyped and followed at scheduled visits through 78 weeks for relapses. Twenty‐eight dichotomous and continuous variables were assessed at baseline and week 12, including phenotype, inflammatory markers, disease activity (PCDAI) and other markers. Clinical relapses defined as PCDAI >10 after remission were recorded using a relapse form. Logistic regression & risk modelling was performed. Results: We enrolled 282 eligible patients of whom 178 (63.6%) patients achieved steroid free remission by week 12. Disease complications developed in 22/76(29%) of patients with relapse compared to 20/206 (9.7%) without relapse ( P = 0.01). Multivariable analysis demonstrated that while variables from age/gender at diagnosis were not predictive, week 12 variables including PCDAI >5 ( P = 0.02), CRP >20 mg/L ( P = 0.02), and faecal calprotectin >400 µg/g ( P = 0.03) as optimal cut‐offs were associated with increased risk of relapse. A prediction model for patients in remission including gender, age, week 12 PCDAI, calprotectin and CRP had sensitivity 43%, specificity 92%, PPV 78%, NPV 71% for relapse. Conclusions: Early relapses were associated with a higher risk for disease complications at followup. Relapse prediction based on week 12 disease activity or inflammation is superior to prediction using data from diagnosis. Abstract : LINKED CONTENT This article is linked to Lemberg and Day paper. To view this article visit https://doi.org/10.1111/apt.15069 .